2006
DOI: 10.1007/s11095-006-0136-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Basic Fibroblast Growth Factor Correlates with Resistance to Paclitaxel in Human Patient Tumors

Abstract: These results support a role of bFGF in paclitaxel resistance in human patient tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
58
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 42 publications
(22 reference statements)
2
58
0
4
Order By: Relevance
“…They also reported that treatment with an FGF2 antibody could inhibit FGF2-dependent proliferation and angiogenesis. Furthermore, Gan and colleagues reported that high FGF2 tumor levels reduced drug sensitivity, in part, due to the direct effects of FGF2 on proliferation and apoptosis (40). FGF2 activates the PI3K in endothelial cells (41), which regulate Akt or protein kinase B (PKB) activity (42).…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that treatment with an FGF2 antibody could inhibit FGF2-dependent proliferation and angiogenesis. Furthermore, Gan and colleagues reported that high FGF2 tumor levels reduced drug sensitivity, in part, due to the direct effects of FGF2 on proliferation and apoptosis (40). FGF2 activates the PI3K in endothelial cells (41), which regulate Akt or protein kinase B (PKB) activity (42).…”
Section: Discussionmentioning
confidence: 99%
“…31 Although these factors increase BCSC selfrenewal, they may also activate survival pathways which can artificially increase drug resistance. 41,42 Nanofiber scaffolds may offer an alternative to mammosphere culture as a way to propagate BCSC in vitro. The composition of these fibers can be controlled or modified to either inhibit or promote cellular differentiation.…”
mentioning
confidence: 99%
“…Some previous studies have shown that bFGF prevents chemotherapy induced apoptosis, which result in chemoresistance in many cancers such as small cell lung cancer and breast cancer. This antiapoptotic effect is mediated by MAPK/ERKs, PI3K/AKT and/ or PKC that increase the expression and activation of several anti-apoptotic proteins including Bcl-2, Bcl-X L and XIAP (16,17). Although the precise mechanisms of drug resistance in melanoma cells are largely unknown, targeted inhibition of bFGF/FGFR-1 in primary and metastatic melanoma cells blocks tumor growth by inducing apoptosis indicating a critical pro-survival role of bFGF in melanoma (7).…”
Section: Discussionmentioning
confidence: 99%